2020
DOI: 10.1024/1662-9647/a000228
|View full text |Cite
|
Sign up to set email alerts
|

I Feel You, We Can Do This

Abstract: Abstract. We investigated whether similarity between partners in positive and negative affect is associated with the perception that one manages everyday life well together as a couple (dyadic mastery). To this end, we used data from 99 older couples (mean age = 75 years; mean length of relationship = 45 years) obtained 5 times a day over 7 consecutive days as participants went about their everyday lives. Analyses using actor-partner interdependence models revealed that higher (average and momentary) similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…That convergent lows were less predictive of relationship functioning than convergent highs is consistent with prior research demonstrating mixed effects of shared negative affect (Brown et al, 2022; Schade et al, 2020). One explanation is that the relational processes underlying shared negative affect can be divergent.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…That convergent lows were less predictive of relationship functioning than convergent highs is consistent with prior research demonstrating mixed effects of shared negative affect (Brown et al, 2022; Schade et al, 2020). One explanation is that the relational processes underlying shared negative affect can be divergent.…”
Section: Discussionsupporting
confidence: 86%
“…The benefits of emotional similarity have since been well documented in relationships research. Many studies found positive associations between partners' momentary affect similarity and perceptions of the relationship, such as feelings of love and perceived partner responsiveness (Sels et al, 2020), a sense of managing life well with one's partner (Schade et al, 2020), positive feelings about the relationship (Levavi-Francy et al, 2020), and relationship satisfaction (Brown et al, 2022). However, because these studies rarely asked individuals what their emotions were about, their results may attest more to the benefits of developing similar affective patterns than to the implications of responding to particular events in similar ways.…”
Section: Convergence In Emotional Highs and Lowsmentioning
confidence: 99%
See 1 more Smart Citation